Train your mind, change your brain : how a new science reveals our extraordinary potential to transform ourselves - Begley, Sharon, 1956-2021- (Ballantine Books, 2007)
Neuroscience long held that the hardware of the brain is immutable--that we are stuck with what we were born with. As science journalist Begley shows, however, recent pioneering experiments in the new science of neuroplasticity reveal that the brain is capable not only of altering its structure but also of generating new neurons, even into old age. The brain can adapt, heal, renew itself after trauma, and compensate for disability. Begley documents how this paradigm shift is transforming both our understanding of the human mind and our approach to deep-seated emotional, cognitive, and behavioral problems. These breakthroughs show that it is possible to reset our happiness meter, regain the use of limbs disabled by stroke, train the mind to break cycles of depression and OCD, and reverse age-related changes in the brain. They also suggest that it is possible to teach and learn compassion.--From publisher description.